Catalytic Isohypsic‐Redox Sequences for the Rapid Generation of Csp3‐Containing Heterocycles. Issue 65 (2nd November 2018) - Smith, Craig D.; Phillips, David; Tirla, Alina; France, David J.
Abstract: Cross‐coupling reactions catalyzed by transition metals are among the most influential in modern synthetic chemistry. The vast majority of transition‐metal‐catalyzed cross‐couplings rely on a catalytic cycle involving alternating oxidation and reduction of the metal center and are generally limited to forging just one type of new bond per reaction (e.g., the biaryl linkage formed during a Suzuki cross‐coupling). This work presents an Isohypsic‐Redox Sequence (IRS) that uses one metal to effect two catalytic cycles, thereby generating multiple new types of bonds from a single catalyst source. We show that the IRS strategy is amenable to several widely used transformations including the Suzuki–Miyaura coupling, Buchwald–Hartwig amination, and Wacker oxidation. Furthermore, each of these reactions generates value‐added heterocycles with significant sp 3 ‐C (3‐dimensional) content. Our results provide a general framework for generating complex products by using a single metal to fulfill multiple roles. By uniting different combinations of reactions in the isohypsic and redox phases of the process, this type of catalytic multiple bond‐forming platform has the potential for wide applicability in the efficient synthesis of functional organic molecules. Abstract : Coupling reactions catalyzed by transition metals are tremendously influential in modern synthetic chemistry. These reactions typically involve redox cycling at the metal center and are generally limited to forging just one type of new bond per reaction. This work presents an isohypsic‐redox sequence (IRS) that uses one metal to effect two catalytic cycles, thereby generating multiple new types of bonds from a single catalyst source.